Psychometric properties of the English version of DASS in a sample of Malaysian nurses - Hariyati Shahrima Abdul Majid; Harris Shah Abd Hamid; Azlin Hj Alwi; Muhamad Karimi Sulaiman (Penerbit Universiti Kebangsaan Malaysia, 2019)
The Malay version of DASS (Depression, Anxiety and Stress Scale) had been tested with samples in the general and clinical population in Malaysia. However, this Malay version was found to have lower sub-scales reliabilities than the comparable English version tested in a non-Malaysian sample. Additionally, the translators observed that there are no cultural-specific issues regarding the scale. Therefore, the English version of DASS might be more appropriate to be used in the Malaysian private hospitals where the use of English is widespread. This study examines the original English version of DASS in a sample of 521 nurses in private hospitals in the Klang Valley area. The psychometric properties will be examined using a measurement model in AMOS. The steps involved are examination of the unidimensionality of the subscales, reliability (alpha Cronbach and AVE), and validity (AVE, Fitness Indices, and Modification Indices). The findings are discussed in terms of the use of different languages in psychological testing.